Pathogenesis and management of TRPV3-related Olmsted syndrome - Lu, Antong; Li, Kezhen; Huang, Cong; Yu, Bo; Zhong, Weilong (Frontiers in Genetics, 2024)
Olmsted syndrome is characterized by symmetrically distributed, destructive, inflammatory palmoplantar keratoderma with periorificial keratotic plaques, most commonly due to gain-of-function mutations in the transient receptor potential vanilloid 3 (TRPV3) gene, which involves multiple pathological functions of the skin, such as hyperkeratosis, dermatitis, hair loss, itching, and pain. Recent studies suggest that mutations of TRPV3 located in different structural domains lead to cases of varying severity, suggesting a potential genotype-phenotype correlation resulting from TRPV3 gene mutations. This paper reviews the genetics and pathogenesis of Olmsted syndrome, as well as the potential management and treatment. This review will lay a foundation for further developing the individualized treatment for TRPV3-related Olmsted syndrome.